STUDENTS’ MOTIVATION IN LEARNING ENGLISH AS A FOREIGN LANGUAGE: A CASE STUDY AT ENGLISH EDUCATION STUDY PROGRAM IN UNIVERSITAS ISLAM BATANG HARI - Sulistyowati; Harlina Harja; Adang Ridwan; Daris (STKIP Subang, 2026)
English plays a significant role as a global language and has become an essential subject in higher education. However, university students demonstrate different levels of motivation in learning English as a foreign language (EFL), which may influence their learning outcomes. This study aimed to explore students' motivation in learning English at the English Education Study Program of Universitas Islam Batang Hari. A qualitative case study design was employed involving three highly motivated students selected through purposive sampling. Data were collected through observations, semi-structured interviews, and documentation and analyzed using Creswell's qualitative data analysis procedures. The findings reveal that students' motivation was influenced by both intrinsic and extrinsic factors. Intrinsic motivation emerged from students' personal interests, self-development, and future aspirations, whereas extrinsic motivation was strengthened through family support, lecturers, peers, digital media, and the academic environment. These findings indicate that meaningful learning experiences and supportive social relationships contribute significantly to sustaining students' motivation in learning English. This study provides insights for lecturers to create more motivating English learning environments in higher education.